LEGAL POLICY ON HUMAN TRAFFICKING CRIMES - Prakoso, Abdul Rahman; Nurmalinda, Putri Ayu (Universitas Negeri Semarang (UNNES), 2018)
The crime of trafficking in persons is still a problem in people's lives. Trafficking of persons undertaken includes the process of hiring up to the act of buying and selling people. The existence of Law Number 21 Year 2007 concerning the Eradication of Crime of Trafficking in Persons as protection for trade acts. The legal policy in the realm of human trafficking is not only about central government elements but also related to the policies issued by the local government. The law as an existing regulatory instrument in Indonesia is based on the existence of regional policy to protect its citizens. Trafficking can not be separated from various parties. This concerns various aspects of the community elements involved in it. There is a need for comprehensive prevention to avoid trafficking. In this case both the office and the law enforcers must play a role in the prosecution and protection of trafficking. Keywords: Policy, people trafficking, protection